The effect of complex load on the reliable operation of solar photovoltaic and wind power stations integrated into energy systems and into off-grid energy areas - Pavel V. Ilyushin; Olga V. Shepovalova; Sergey P. Filippov; Anton A. Nekrasov (Energy Reports, 2022)
A mass renewable power stations commissioning, first of all solar photovoltaic stations (SPVS) and wind power stations (WPS) shall be associated with the properly implemented complex load modeling while calculating their electric operation modes. This article deals with the basic failures of standard algorithm of SPVS and WPS invertors/converters, Fault Ride Through (FRT), that has to reduce the active power output and to increase that of reactive power, in case of voltage drop. In order to prevent outages of SPVS and WPS equipment during emergency disturbances, the trip set points of SPVS and WPS inventors/converters shall be adjusted to those of the adjacent power network protective relay. In this article, an approach to selecting methods for complex loads modeling, in industrial energy areas, has been developed. A method for calculating the value of critical voltage across the load bars has been considered, and the relevancy to apply the dynamic scale model of electric motor has been substantiated. The specific aspects of the voltage-dependent and frequency-dependent load static characteristics employment, in calculations of electromechanical transient processes, have been analyzed. Recommendations on representing electric motors integrated into complex load circuits, in various software packages designed for operation modes calculations, have been stipulated. Various methods making it possible to take account of electromagnetic transient processes, in rotors of asynchronous motors, have been described. A proper account of complex loads enables to ensure reliable functioning of SPVS and WPS integrated into energy systems and operating in isolated energy areas avoiding their outages including those disturbances in power supply of power consuming equipment of industrial areas.